Songbased rival assessment in songbirds - Linhart, Pavel (Jihočeská univerzita, 2014)
This study shows the importance of the basic spectro-temporal song parameters in territorial contests between male songbirds. Chiffchaff and willow warbler were selected as model species for their phylogenetic and ecological similarity, strong territorial behaviour, but very different singing styles. We found that bigger males of both species sing lower pitched songs and that males of both species adjust their behaviour according to song pitch of their rival simulated by playback. Thus, it seems that both species use song pitch to acoustically assess the body size of their rivals. We also show that song length and syllable rate are important features of the song, probably signalling short-term motivation to escalate territorial conflict.
Songbased rival assessment in songbirds
Keywords: male-male competition; acoustic communication resource holding potential; fighting ability; songbird; chiffchaff; willow warbler; male-male competition; acoustic communication resource holding potential; fighting ability; songbird; chiffchaff; willow warbler